2017
DOI: 10.1590/1677-5449.008916
|View full text |Cite
|
Sign up to set email alerts
|

Análise dos fatores de risco relacionados às amputações maiores e menores de membros inferiores em hospital terciário

Abstract: Background: Whether they are defined as minor or major, lower limb amputations constitute a severe health problem, causing high rates of morbidity and mortality and considerable social impact. Different patient clinical characteristics appear to be related to different types of amputations. Objectives: To analyze risk factors present in patients who underwent lower limb amputations at a tertiary hospital. Methods: This was a retrospective, cross-sectional study of 109 patients who underwent lower limb amputati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 31 publications
1
19
0
10
Order By: Relevance
“…16 In contrast, LL amputations are more common among older people and are mostly related to non-traumatic causes, such as DM and vascular diseases. 3,10,17,18 In this study, upper limb amputations accounted for a much lower percentage than LL amputations, involved a younger age group, and the majority were caused by traumatic events.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…16 In contrast, LL amputations are more common among older people and are mostly related to non-traumatic causes, such as DM and vascular diseases. 3,10,17,18 In this study, upper limb amputations accounted for a much lower percentage than LL amputations, involved a younger age group, and the majority were caused by traumatic events.…”
Section: Discussionmentioning
confidence: 62%
“…It was found that the majority of patients who underwent amputations were elderly, which is a similar result to those of previous studies of amputation, particularly non-traumatic amputations. 3,9,10 In this study, the majority of amputated patients were male, which may be because men are less likely to seek health care, are more exposed to risk situations, and are more likely to neglect their health care. 11 A study conducted in the United States showed that men are more likely to undergo LL amputations and suggested that women have higher mortality rates associated with these amputations, both of which were characteristics also observed in this study.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Indivíduos com maior vulnerabilidade e alta exposição ao stress apresentam maior resiliência, graças a capacidade de ajustamento e adaptação perante a uma situação de vulnerabilidade. [31][32][33][34] O Diabetes Mellitus e a Hipertensão Arterial Sistêmica foram significativas nos amputados e cerca de 35 Borges 36 e podem indicar um risco para novas amputações. Segundo a Carga Global de Doença (GBD -Global Burden of Diseases) essas comorbidades estão associadas a um aumento de incapacidades e consequentemente de anos de vida sadia perdidos.…”
Section: Discussionunclassified